Dampak Tunjangan Sertifikasi terhadap Kinerja Guru - Ramadhan, Muamar; Darmoko, Puji Dwi; fariyati, Sri; ., Muntoha (Madaniyah, 2017)
Teacher certification is one form of implementation of Law No. 14 Year 2005 on Teachers and Lecturers. Teachers categorize as a profession because it has met the requirements of the profession, the position includes intellectual activity; position control of certain scientific and educated in a certain qualifications; office promising career; position altruistic service; and positions that have professional organizations. Teacher certification should ideally have an impact on teacher performance. Teacher certification should ideally have an impact on teacher performance. The field researchÂ  type of quantitative correlation with model analysis SPSS proves how the relationship and influence between alone certification and performance of teachers at teacher SMP/MTs and SD/MI certified in Pemalang district spread over 1,029 educational institutions both SD/MI and SM /MTs.